The primary application of indocyanine green fluorescence imaging in surgical oncology - Dai, Zhang-Yi; Shen, Cheng; Mi, Xing-Qi; Pu, Qiang (Frontiers in Surgery, 2023)
Indocyanine green (ICG) is a non-toxic, albumin-bound, liver-metabolized fluorescent iodide dye and has been widely utilized in clinical applications since the mid-1950s. However, after the 1970s, in-depth research on the fluorescence properties of ICG greatly expanded its application in the medical field. In our mini-review, we reviewed papers on ICG in primary oncology surgery. In addition, the application of targeted ICG photothermal technology in tumor therapy is briefly mentioned.